Metabolomics Profiling of Age-associated Metabolites in Malay Population - Jen Kit Tan; Siti Nor Asyikin Zakaria; Geetha Gunasekaran; Nur Fathiah Abdul Sani; Muhammad Luqman Nasaruddin; Faizul Jaafar; Zulzikry Hafiz Abu Bakar; Ahmad Imran Zaydi Amir Hamzah; Khairun Nain Nor Aripin; Mohd Dzulkhairi Mohd Rani; Hanafi Ahmad Damanhuri; Musalmah Mazlan; et al. (Hindawi, 2024)
Indexed by Scopus/ERA